Utilising Diagnostic Assessment of Learner Mentality to Foster Challenge-Readiness in Chemistry Learning - Dewi Satria Ahmar; Muhammad Fath Azzajjad (Athena: Journal of Social, Culture and Society, 2026)
The global scientific education community is recognizing that students' success in challenging subjects such as chemistry is contingent not only upon cognitive capabilities but also on psychological readiness to confront academic challenges. This study seeks to implement a diagnostic evaluation of learner mentality to characterize students' readiness to confront challenges in chemistry education and to discern essential psychological factors that facilitate or impede adaptive engagement. The study concentrated on evaluating five aspects of learner mentality: persistence, self-confidence, challenge orientation, feedback responsiveness, and emotional regulation among undergraduate chemistry education students, aiming to yield data-driven instructional implications. The urgency of this research is underscored by the persistent disparity between students' conceptual proficiency and their psychological readiness to navigate complex, abstract, and cognitively demanding chemistry content. If teachers don't know how students are mentally preparing for class, they might only deal with surface-level academic problems and ignore deeper emotional and motivational problems that affect students' ability to stay engaged and bounce back. The results show that most students (69.7%) were either Challenge-Ready or Highly Challenge-Ready. The mean score for Feedback Responsiveness (M = 3.90) was the highest, and the mean score for Emotional Regulation (M = 3.51) was the lowest. There were strong links found between persistence and challenge orientation (r = 0.45) and between self-confidence and emotional management (r = 0.38). These findings indicate that enhancing self-confidence and emotional regulation should be prioritized. Subsequent research should investigate intervention-based methodologies to enhance psychological readiness in conjunction with conceptual chemistry education.